Wayfaring in Taiwan during COVID-19: Reflections on Political Ontologies of Disease and Geopolitics - Simon, Scott (Anthropologica, 2021)
What are the political and ontological implications of COVID‑19? I had plenty of time to reflect on this from March to July after I ended fieldwork in Guam and unexpectedly spent four months in Taiwan. Because of Taiwan’s proximity to China, where the pandemic began, it initially seemed as if it would be among the most serious cases. Instead, Taiwan’s public health measures allowed it to become one of the few places in the world relatively untouched by the virus. The experience of Taiwan with COVID‑19 was shaped most of all by tense relations with China and the non-recognition of the country by the World Health Organization (WHO). There are also intriguing differences within Taiwan where historically Chinese settler groups and Indigenous peoples related to other Pacific Islanders find their place in the world through a broad spectrum of non-Western ontologies. In travelogue genre, I reflect upon their different stories and practices of worlding as fears of the pandemic contributed to a heightened sense of crisis, ethnic tensions, and a rise in nationalism. This reveals important ontological differences that will continue to influence the geopolitics of the region even beyond the current pandemic.